Динаміка психічних станів цивільних громадян під час воєнних дій в Україні - Жданова, І. В.; Zhdanova, I. V.; Шахова, О. Г.; Shakhova, O. H.; Роденкова, В. А.; Rodenkova, V. A.; Жданова Iрина Вячеславiвна (Вісник Харківського національного університету імені В. Н. Каразіна. Сер.: Психологія. - 2023. - Вип. 74. - С. 7-12, 2023)
У статті представлено результати дослідження динаміки психічних станів цивільних громадян Східного регіону України під час воєнних дій на території України в перший рік війни. Встановлено, що на початку воєнних дій в Україні найбільш типовими психічними станами цивільних громадян були страх, розгубленість, безпорадність, смуток, депресія, паніка, роздратованість і гнів, тобто, типові для гострого переживання травмівної стресової ситуації психічні стани. Через рік від початку війни респонденти відзначали суттєве зниження частоти переживання страху, розгубленості та паніки. Водночас частими станами стали смуток, депресія, втома, виснаженість, тривога та роздратованість - тобто психічні стани, які свідчать про знижений енергетичний потенціал населення, загрозу виникнення нових страхів та спалахів роздратування. Все це може призводити до порушень міжособистісних відносин, професійної дезадаптації, розвитку психосоматичних та посттравматичних розладів. В той же час, у певної категорії населення з’явився інтерес до життя, «захисна байдужість», спокій. Результати дослідження можуть бути використані при розробці психотехнологій щодо мінімізації наслідків травм, пов’язаних з війною, а також для збереження та підтримки психічного здоров’я населення в умовах війни та у довгостроковій перспективі.

The article presents the results of the mental states dynamics study in the Eastern region civilians of Ukraine during the Russian military aggression on the territory of Ukraine in the first year of the war. The paper substantiates the relevance of the study of the mental states of the civilian population in the context of maintaining mental health problem and preventing post-traumatic stress disorders. War is a prolonged traumatic situation during which episodes of a threat to life and health occur with a certain frequency, and this affects the dynamics of the mental states of the civilian population. An additional traumatic effect on the psyche is exerted by the information and psychological warfare that people are exposed to through Internet technologies. The study found that at the beginning of hostilities in Ukraine, the most typical mental states of civilians in the eastern regions of Ukraine were fear, confusion, helplessness, despondency, depression, panic, irritability and anger. These mental states are typical of the acute experience of a traumatic stressful situation. A year after the start of the war, respondents noted a significant decrease in the frequency of experiencing fear, confusion and panic. At the same time, sadness, depression, fatigue, exhaustion, anxiety, and irritability became common. These are mental states that testify to the reduced energy potential of the population, the danger of new fears and outbursts of irritation. The consequence of this may be a violation of interpersonal relationships, professional maladjustment, the development of psychosomatic and post-traumatic disorders. At the same time, a number of respondents showed an interest in life, "protective indifference", peace. The results of the study can be used in the development of psychotechnologies to minimize the consequences of war-related injuries, as well as to preserve and support the mental health of the population in war conditions and in the long term.

В статье представлены результаты исследования динамики психических состояний гражданских граждан Восточного региона во время военных действий на территории Украины в первый год войны. Установлено, что в начале военных действий в Украине наиболее типичными психическими состояниями гражданских граждан были страх, растерянность, беспомощность, уныние, депрессия, паника, раздражительность и гнев, то есть типичные для острого переживания травмирующей стрессовой ситуации психические состояния. Через год после начала войны респонденты отмечали существенное снижение частоты переживания страха, растерянности и паники. В то же время частыми состояниями стали уныние, депрессия, усталость, истощенность, тревога и раздраженность - то есть психические состояния, свидетельствующие о сниженном энергетическом потенциале населения, угрозе возникновения новых страхов и вспышек раздражения. Все это может приводить к нарушениям межличностных отношений, профессиональной дезадаптации, развитию психосоматических и посттравматических расстройств. В то же время, у определенной категории населения появился интерес к жизни, «защитное безразличие», покой. Результаты исследования могут быть использованы при разработке психотехнологий минимизации последствий травм, связанных с войной, а также для сохранения и поддержания психического здоровья населения в условиях войны и в долгосрочной перспективе.
Mental states dynamics in civilians during the war in Ukraine
Keywords: психічні стани; травматична ситуація; психічна травма; війна; Україна; цивільні громадяни; mental states; traumatic situation; mental trauma; war; Ukraine; civilian citizens; психические состояния; травматическая ситуация; психическая травма; война; Украина